Patterns of failure in head and neck cancer patients treated with intensity modulated radiation therapy: editorial response - Leeman, Jonathan E.; Lee, Nancy; Riaz, Nadeem (Translational Cancer Research, 2017)
We thank Dr. van der Veen and Dr. Nuyts for their thoughtful discussion and commentary on our recent manuscript as well as placing our results in the broader context of the evolution of target delineation and dosing regimens in head and neck radiotherapy. We herein provide additional clarification to address their comments.